2013
DOI: 10.1002/aic.14090
|View full text |Cite
|
Sign up to set email alerts
|

Reactive adsorption for the selective dehydration of sugars to furans: Modeling and experiments

Abstract: 5-hydroxymethylfurfural (HMF) can be produced from the acid-catalyzed dehydration of fructose but its yield is limited due to subsequent HMF degradation to side products. A reactive adsorption process is proposed to improve the yield to HMF. Separate experimental singlecomponent isotherms of fructose, HMF, formic acid, and levulinic acid on carbon BP2000 and reaction kinetics of the fructose dehydration to HMF in aqueous solution of HCl are presented to develop empirical isotherms and kinetic rate constants, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
4
21
0
Order By: Relevance
“…[15,33] Considering the analysiss tep-by-step, the positive effect of combining heterogeneousa nd homogeneous catalysts is in agreement with the increase in all the direct reactions, with the main effect observed when using the b-zeolite. It mustb eh ighlightedt hat, in good agreement with the initial hypothesis, all these coefficients are higher than the previously reported ones considering ak inetic model based on adsorption equilibria.…”
Section: Resultssupporting
confidence: 66%
“…[15,33] Considering the analysiss tep-by-step, the positive effect of combining heterogeneousa nd homogeneous catalysts is in agreement with the increase in all the direct reactions, with the main effect observed when using the b-zeolite. It mustb eh ighlightedt hat, in good agreement with the initial hypothesis, all these coefficients are higher than the previously reported ones considering ak inetic model based on adsorption equilibria.…”
Section: Resultssupporting
confidence: 66%
“…Unfortunately, the acid-catalyzed environment is also propitious to HMF's rehydration to levulinic acid and formic acid and parallel reactions of fructose to humin other than HMF. [82] These are the main constructions for economical HMF production. To address these drawbacks, many methods have been developed to improve the performance.…”
Section: Hmfmentioning
confidence: 99%
“…It was found that reactive adsorption can be a promising process for not only the production of HMF but also any aqueous-phase chemistry where the desired product is an intermediate in a reaction cascade. [82] DMSO is a kind of high boiling point organic solvent. The method of adsorption was subsequently studied for the separation of HMF and DMSO.…”
Section: Hmfmentioning
confidence: 99%
“…58 In several studies, reactive adsorption has been dealt like 59 adsorption without considering the reaction part. Indeed, reactive 60 adsorption increases the rate of production/degradation by a 61 significant proportion as compared to simple adsorption [19,23]. 62 The advantage of reactive adsorption over simple adsorption is that 63 reaction and separation occurs simultaneously during adsorption 64 in a single unit operation [9].…”
Section: Introductionmentioning
confidence: 98%
“…Methylene 20 blue (MB) is a cationic dye which has widespread use in textile 21 industries [5]. Several methods are used for dye removal for instance, 22 adsorption, biological treatment, ion exchange, oxidative processes, 23 membrane filtration, irradiation and electrokinetic coagulation [6,7]. 24 Among all other physicochemical methods, adsorption is the 25 superior technique owing to its easy availability, low cost, high 26 efficiency, ease of operation and ability to treat more concentrated 27 dyes [8].…”
Section: Introductionmentioning
confidence: 99%